Cloaked Caged Compounds: Chemical Probes for Two‐Photon Optoneurobiology. (2nd December 2016) - Richers, Matthew T.; Amatrudo, Joseph M.; Olson, Jeremy P.; Ellis‐Davies, Graham C. R.
Abstract: Caged neurotransmitters, in combination with focused light beams, enable precise interrogation of neuronal function, even at the level of single synapses. However, most caged transmitters are, surprisingly, severe antagonists of ionotropic gamma ‐aminobutyric acid (GABA) receptors. By conjugation of a large, neutral dendrimer to a caged GABA probe we introduce a "cloaking" technology that effectively reduces such antagonism to very low levels. Such cloaked caged compounds will enable the study of the signaling of the inhibitory neurotransmitter GABA in its natural state using two‐photon uncaging microscopy for the first time. Abstract : Maskierte Neurotransmitter wirken antagonistisch gegen den GABA‐A‐Rezeptor. Die Konjugation von photoaktivierbarem DEAC450‐GABA an ein Polyester‐Dendrimer senkt dessen antagonistische Wirkung deutlich. Die chemische Sonde war in den Konzentrationen für effektive Zwei‐Photonen‐Photolyse in lebenden Zellen ohne biologische Wirkung.